High-modulus strong-adhesion injectable hydrogel as well as preparation method and application thereof

Through wild silk protein and modified polysaccharide cross -linking can be injected with hydrogel, solve the problem of low existing hydrogel molding, adhesion, weakness, and non -anti -inflation. The effect is suitable for a variety of organization repair.

CN119367585APending Publication Date: 2025-01-28LIANGZHU LAB

Patent Information

Application Number
CN202411462815.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-19
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing injectable hydrogels have low modulus, weak adhesion, and are not resistant to swelling, and cannot be mechanically adapted to high modulus defects, resulting in further damage to stress-concentrated tissue.

Method used

Using wild silk protein and modified polysaccharides to prepare high -modular adhesive hydrogel, to form an insoluble fluid gel with pre -association, and use body temperature to trigger the in situ of the assembly to form a strong water gel Essence

Benefits of technology

The amount of hydrogel reaches 10.7MPa and the adhesive strength reaches 160kPa. It can resist dissolving and lubrication. It is suitable for a variety of tissue repair, including arthroscopy surgery and suture -free skin repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367585A_ABST
    Figure CN119367585A_ABST
Patent Text Reader

Abstract

The invention provides a high-modulus strong-adhesion injectable hydrogel, and belongs to the field of biological materials, the hydrogel is the injectable hydrogel with the highest modulus at present, the modulus is up to 10.7 MPa, the modulus is adjustable, the adhesion strength also reaches 160kPa, and the hydrogel can well simulate tissues with different moduli such as skin and cartilage; meanwhile, the hydrogel can also resist swelling and lubricate. The invention provides a preparation method of the hydrogel, which comprises the following steps: mixing a silk protein solution of the wild silkworm silk and the modified polysaccharide in proportion, pre-crosslinking, and further crosslinking by utilizing temperature, so as to obtain the hydrogel with high modulus and strong adhesion. According to the hydrogel, firstly, fibroin and polysaccharide are mixed to form water-insoluble fluid gel, the water-insoluble fluid gel can be used for underwater injection in arthroscopic surgery, and then body temperature triggers assembly to form tough hydrogel in situ. In addition, the invention also proves that the hydrogel can be used for suture-free skin repair and can effectively avoid wound disintegration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomaterials, and in particular relates to a high-modulus, strong-adhesion injectable hydrogel and a preparation method and application thereof. Technical Background

[0002] At present, tissue repair mainly relies on implants, including stents, patches, injectable hydrogels, etc. Injectable hydrogels are considered to be the most promising implants due to their advantages such as minimal invasiveness and better adaptability to defects. However, at present, the load-bearing level of injectable hydrogels made of natural or synthetic polymer materials only reaches 200kPa, which is difficult to reach the 1-5MPa level of human body load-bearing tissues. Therefore, injectable hydrogels cannot achieve mechanical adaptation to high modulus defects, resulting in further damage to stress-concentrated tissues.

[0003] Silk is one of the strongest fibers in nature. Due to its excellent mechanical properties, good biocompatibility, and biodegradability, it has been widely used in high-performance materials such as biomedical materials in recent years. Natural silk is divided into mulberry silk and wild silk, the latter including tussah silk, castor silk, silkworm silk, camphor silk, etc. In addition to the differences in sources, dissolution and extraction processes, the primary structures of mulberry silk fibroin and wild silk fibroin are also different. The β-folding sequence of mulberry silk fibroin is glycine-alanine-glycine-alanine-serine (GAGAGS), which is relatively stable and requires high temperature or long-term treatment with organic solvents to form; while the β-folding sequence of wild silk fibroin is polyalanine, which can trigger assembly to form β-folding within 10 minutes at human body temperature (about 37°C), so that wild silk fibroin can quickly and gently form hydrogels with stronger mechanical properties in situ compared to traditional silk fibroin. In addition, wild silk fibroin contains a large number of RGD sequences, which are small peptides composed of three amino acids: arginine (Arg, R), glycine (Gly, G) and aspartic acid (Asp, D). They exist in a variety of extracellular matrices and can specifically bind to 11 integrins, effectively promoting cell adhesion to biomaterials. Therefore, compared with traditional silk fibroin, wild silk fibroin is more likely to promote cell adhesion and accelerate tissue regeneration.

[0004] The Chinese patent "Injectable natural silk nanofiber composite hydrogel and preparation method thereof" (publication number: CN117586533A) provides an injectable natural silk nanofiber composite hydrogel and a preparation method thereof, which is to mix a natural silk nanofiber suspension with a tyramine-modified hyaluronic acid solution, and use horseradish peroxidase and hydrogen peroxide as a catalytic system to form multiple covalent crosslinks between fiber-fiber, fiber-hyaluronic acid, and hyaluronic acid-hyaluronic acid. However, the compressive strength of the hydrogel prepared by this method can only reach 10kPa, the silk nanofibers cannot be further assembled into toughened colloids, and the introduction of double tyrosine bonds that do not exist in the body is not conducive to clinical transformation.

[0005] In view of the above-mentioned deficiencies of wild silkworm silk products and technologies, the purpose of the present invention is to provide an injectable high modulus, strong adhesion, anti-swelling, lubricating silk fibroin and polysaccharide hydrogel to solve the problems that the current injectable hydrogel cannot simultaneously overcome, such as low modulus, weak adhesion, and no anti-swelling. At the same time, the biomimetic components of the protein and polysaccharide used are similar to the components of the extracellular matrix of the body, so it is called tissue biomimetic glue. Summary of the invention

[0006] In view of the above problems, the present invention provides a high modulus and strong adhesion injectable hydrogel, which belongs to the field of biomaterials. The hydrogel is the injectable hydrogel with the highest modulus at present, up to 10.7MPa, and the modulus is adjustable, and the adhesion strength also reaches 160kPa, which can well simulate the tissues with different moduli such as skin and cartilage; at the same time, the hydrogel can also resist swelling and lubrication. The present invention provides a preparation method of the hydrogel, and the wild silk fibroin solution and the modified polysaccharide are mixed in proportion for pre-crosslinking, and then further crosslinked by temperature to obtain a high modulus and strong adhesion hydrogel; the hydrogel is first formed into a water-insoluble fluid gel by mixing silk fibroin and polysaccharide, which can be used for underwater injection in arthroscopic surgery, and then the body temperature triggers the assembly in situ to form a strong hydrogel. In addition, the present invention also confirms that the hydrogel can be used for suture-free skin repair, which can effectively prevent the wound from collapsing.

[0007] On the one hand, the present invention provides a high modulus and strong adhesion injectable hydrogel, wherein the injectable hydrogel is prepared by cross-linking wild silk fibroin and modified polysaccharide.

[0008] At present, the modulus of injectable hydrogels is generally low, and most of them are prepared with silk as raw materials; wild silk is rarely used to prepare hydrogels because of its complex extraction process of high molecular weight silk fibroin and difficult to preserve stably. Even if wild silk is added during the preparation process, its content is extremely low or low molecular weight wild silk fibroin, while the wild silk content in the hydrogel provided by the present invention is as high as 45%. The higher the content of wild silk fibroin protein, the higher the modulus; compared with ordinary mulberry silk, the amino acid sequence of the β-fold of wild silk fibroin protein is polyalanine, and the β-fold structure is unstable and easily affected by temperature. Therefore, the hydrogel prepared with wild silk has temperature sensitivity, so that it can be cross-linked and cured at room temperature without the need for other physical and chemical cross-linking methods, which greatly guarantees the clinical transformation potential of the hydrogel.

[0009] Furthermore, the wild silk includes any one or more of tussah silk, castor silk, natural silk and camphor silk.

[0010] In some specific embodiments, tussah silk, ricinus silk, celastrus silk and camphor silk can be miscible in any proportion to prepare an injectable thermosensitive enhanced hydrogel.

[0011] In some specific embodiments, the hydrogel is prepared using any one of wild silks selected from the group consisting of tussah silk, castor silk, cerambycid silk and camphor silk. Preferably, tussah silk fibroin is used.

[0012] Furthermore, the modified polysaccharide comprises any one or more of active esterified chondroitin sulfate, active esterified hyaluronic acid, oxidized chondroitin sulfate, oxidized hyaluronic acid, and oxidized dextran.

[0013] The present invention explores the types and modification methods of polysaccharides for preparing hydrogels, and finds that the types of polysaccharides affect the modulus and adhesion of the hydrogels, among which wild silk combined with active esterified chondroitin sulfate has the best effect.

[0014] On the other hand, the present invention provides a method for preparing a high modulus and strong adhesion injectable hydrogel, wherein the preparation method is used to prepare the above-mentioned high modulus and strong adhesion hydrogel.

[0015] Furthermore, the fibroin solution of wild silk and the modified polysaccharide are mixed in proportion.

[0016] Furthermore, the concentration of the silk fibroin solution is 1-50% (w / w), preferably, the concentration range is 1-40%.

[0017] Furthermore, the mixing ratio of the silk fibroin solution to the modified polysaccharide is 1:1-1:100, preferably, the mixing ratio is 1:1-1:10.

[0018] On the other hand, the present invention provides a high modulus and strong adhesion bionic tissue glue, which comprises the above-mentioned hydrogel, in which the wild silk fibroin is pre-cross-linked with modified polysaccharides to make it insoluble in water, and thus the hydrogel can be used for joint cavity injection, because arthroscopic surgery requires flushing water into the joint cavity.

[0019] On the other hand, the present invention provides a use of a hydrogel for preparing a reagent for a cell mixture, characterized in that the hydrogel is the same as described above, and the cells include any one or more of bone marrow mesenchymal stem cells, adipose mesenchymal stem cells, chondrocytes, synovial mesenchymal stem cells, fibroblasts, endothelial cells, epithelial cells, etc., and the cell mixture can be used to treat cartilage defects and skin injuries.

[0020] On the other hand, the present invention provides a use of wild silk for preparing an agent for improving the modulus of injectable hydrogels, wherein the modulus of the hydrogel is 10 kPa-10.7 MPa, which is 10-20 times higher than the modulus of traditional hydrogels.

[0021] The beneficial effects of the present invention include:

[0022] 1. The preparation method provided by the present invention can prepare an injectable hydrogel with the largest modulus. The maximum solid content in the hydrogel can reach 45%, and the modulus is as high as 10.7MPa, which is 10-20 times higher than that of traditional hydrogels; and the adhesion force is as high as 160kPa;

[0023] 2. During the preparation process, the modified polysaccharide is mixed with wild silk fibroin and pre-crosslinked to form a water-insoluble fluid gel, which can be used for underwater injection, such as arthroscopic surgery, repair of narrow deep wounds, etc.;

[0024] 3. The hydrogel provided by the present invention has a temperature-sensitive property because it contains wild silk fibroin. The higher the temperature, the faster it solidifies, that is, the heating device can accelerate the assembly of the hydrogel. Compared with other in vivo cross-linking methods, such as adding organic reagents, adjusting pH and ion concentration, etc., the hydrogel provided by the present invention can be triggered by body temperature to solidify, the process is milder, and does not require the introduction of other chemical substances, and has more clinical transformation prospects;

[0025] 4. Different hydrogels have different crosslinking times. Photocuring is generally considered to be the injectable hydrogel with the strongest mechanical properties. The fastest only requires a few seconds of ultraviolet irradiation, but it requires chemical modification and the addition of photoinitiators, which is not easy to clinically transform. The hydrogel provided by the present invention can be cured in 3 minutes, and the mechanical properties of the hydrogel reach the strongest in about 7 minutes, which is far superior to the currently reported photocured hydrogels.

[0026] 5. The present invention explores the combination of wild silk and different modified polysaccharides to optimize the adhesion of hydrogels, among which wild silk combined with active esterified chondroitin sulfate has the best effect;

[0027] 6. The hydrogel provided by the present invention can be mixed with cells, such as bone marrow mesenchymal stem cells, etc., and used to load cells to achieve the effect of in situ tissue repair by in situ injection. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 :Schematic diagram of preparing hydrogel by mixing silk fibroin solution and modified polysaccharide

[0030] Figure 2: Rheological properties of the biomimetic glue prepared according to the method of Example 1

[0031] Figure 3 : Anti-swelling properties of the biomimetic glue prepared according to the method of Example 1

[0032] Figure 4 : The process of repairing cartilage defects with biomimetic glue

[0033] Figure 5 : Adhesion properties of the biomimetic glue prepared according to the method of Example 1

[0034] Figure 6 : Compression performance of the biomimetic glue prepared by the method of Example 1

[0035] Figure 7 :Effect of biomimetic glue in repairing cartilage defects

[0036] Figure 8 :Bionic glue repairs skin damage

[0037] Fig. 9 :Tissue staining after repair with biomimetic glue DETAILED DESCRIPTION

[0038] The present invention is further described in detail below in conjunction with the accompanying drawings and specific examples of the specification. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0039] Example 1

[0040] This embodiment provides a method for preparing a high modulus injectable hydrogel using wild silk fibroin (including tussah silk, castor silk, silkworm silk and camphor silk, tussah silk fibroin is preferred in this embodiment) and modified polysaccharide (active esterified chondroitin sulfate is preferred in this embodiment) as raw materials, and the specific steps are as follows:

[0041] (1) Preparation of regenerated wild silk fibroin: 50-100g (preferably 50g in this embodiment) silk cocoons or raw silk are degummed in 2L of boiling 0.01-1M (preferably 0.05M in this embodiment) sodium carbonate or sodium bicarbonate solution; the degummed silk is dissolved in 7-15M (preferably 10M in this embodiment) lithium thiocyanate, the bath ratio is 1:1-1:100 (preferably 1:10 in this embodiment), and the dissolution temperature is 25-100°C (preferably 40°C in this embodiment); the solution is then placed in a 2,000-50,000kDa (preferably 30,000kDa in this embodiment) dialysis bag for 5 days, and then freeze-dried into a sponge for use. The lithium thiocyanate solution can be prepared by mixing ammonium thiocyanate and lithium hydroxide in equal moles, adding a large amount of water, heating at 50-120°C, and finally adjusting the pH to 7, and concentrating it into a lithium thiocyanate solution of a specific concentration.

[0042] (2) Preparation of active esterified polysaccharide: 10-30 g (preferably 10 g in this embodiment) of polysaccharide (preferably chondroitin sulfate in this embodiment) is prepared into a (5-20%) solution, and reacted with 1-10 g (preferably 5 g in this embodiment) of EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide) and 1-10 g (preferably 5 g in this embodiment) of NHS (N-hydroxysuccinimide) for 0.5-4 h (preferably 2 h in this embodiment); then the polysaccharide is precipitated with 5-20 times (preferably 10 times in this embodiment) of anhydrous ethanol, repeated 3-5 times, and then freeze-dried; the freeze-dried powder is repeatedly washed several times in a DMF (N,N-dimethylformamide) solution, and then repeatedly washed with anhydrous ethanol, and finally freeze-dried again.

[0043] (3) Figure 1 As shown, 10-40% (w / w) (preferably 30% in this embodiment) silk fibroin solution and 5-30% (preferably 20% in this embodiment) modified polysaccharide solution are mixed in a specific ratio (preferably 1:10 in this embodiment) and the AB liquids are pushed against each other for 10 seconds to prepare an injectable hydrogel, which is then injected into the desired location, such as skin wounds and cartilage defects. Preferably, aminated wild silk fibroin can be used to accelerate its reaction with the modified polysaccharide and shorten the gelation time.

[0044] Preferably, phosphorylcholine solution can be selected as a solvent to dissolve silk fibroin and modified polysaccharides to increase the lubricating effect of the hydrogel, making it more similar to natural cartilage.

[0045] Preferably, a heating device such as infrared heating, a hot air gun, etc. can be selected to shorten the assembly time to a dozen seconds.

[0046] Example 2

[0047] This example measures various properties of the high modulus injectable hydrogel prepared by the method provided in Example 1, and the measuring method is as follows:

[0048] (1) Determination of injectability:

[0049] A rheometer (TA Discovery HR-20) was used to detect the change in the complex viscosity of the biomimetic glue with increasing shear rate; in addition, a 2.5 mL syringe with a 26 G needle was used to press down at a constant speed of 2 mm / min, and the force-time curve was collected.

[0050] (2) Measurement of increased body temperature

[0051] The rheometer was used to verify the change in modulus of biomimetic glue at 37°C. The experiment proved that the modulus of biomimetic glue continued to rise under physiological body temperature, gelling in 3 minutes, and the storage modulus reached a maximum of about 530,000Pa in 8 minutes, which was 4 orders of magnitude higher than the initial storage modulus of about 12Pa, indicating that the effect of body temperature significantly enhanced the modulus of biomimetic glue.

[0052] (3) Determination of anti-swelling

[0053] 20% bionic glue (CC), methacrylate-esterified tussah silk fibroin (ASFMA), and methacrylate-esterified chondroitin sulfate (CSMA) were gelled and swelled in 37°C saline. The water on the surface of the colloid was wiped off at each time point and weighed to calculate the swelling rate.

[0054] (4) Determination of compression modulus

[0055] A cylindrical hydrogel with a diameter of 10 mm and a height of 2 mm was prepared and pressed down at a constant speed of 2 mm / min. The force-displacement curve was collected, and the stress-strain curve was calculated and its slope at the strain of 0-2% was calculated as the compression modulus.

[0056] Figure 2A It shows that as the shear rate increases, the complex viscosity of the biomimetic glue gradually decreases, thus meeting the shear thinning requirements of injectable hydrogels. In addition, in the injection force experiment, a 2.5mL syringe was used to meet the current maximum volume of cartilage hydrogels in clinical practice, and with a smaller needle (26G), only about 6N of force was required to inject the biomimetic glue, demonstrating the excellent injectability of the biomimetic glue.

[0057] Figure 2BIt is shown that at a physiological body temperature of 37°C, the storage modulus and loss modulus of the hydrogel prepared by the method of Example 1 gradually increase, a gel is formed in about 3 minutes, and the modulus reaches the highest at 8 minutes, that is, the silk molecules are basically fully assembled, and the storage modulus of the hydrogel spans 4 orders of magnitude, from a liquid of 12Pa to a solid gel of about 530,000Pa. The temperature-sensitive toughening properties of the bionic glue can enable the bionic glue to achieve a strong and tough effect in situ in the body in a gentle manner.

[0058] Figure 3 The results show that after gelation, the single-component methacrylate hydrogel (ASFMA and CSMA) has obvious swelling, while the biomimetic glue (CC) is a light yellow opaque hydrogel with a small size difference before and after swelling, and almost no swelling. Anti-swelling is an important indicator for hydrogels to maintain mechanical stability and shape stability. Good anti-swelling properties allow in-situ formed hydrogels to remain stable at the required position; on the contrary, hydrogel swelling will lead to mechanical weakening, and the change in properties is not conducive to adhesion and load-bearing. At the same time, the hydrogel may overflow from the defect and cause hydrogel wear or tissue wear.

[0059] Comparative Example 1

[0060] In this comparative example, mulberry silk fibroin was used as raw material to prepare injectable hydrogel. The other components and preparation process of the hydrogel were the same as those described in Example 1.

[0061] Comparative Example 2

[0062] In this comparative example, castor silk fibroin was used as raw material to prepare injectable hydrogel. The other components and preparation process of the hydrogel were the same as those described in Example 1.

[0063] Comparative Example 3

[0064] In this comparative example, cecropin was used as the raw material to prepare the injectable hydrogel. The other components and preparation process of the hydrogel were the same as those described in Example 1.

[0065] Comparative Example 4

[0066] In this comparative example, the injectable hydrogel was prepared using camphor silk fibroin as the raw material. The other components and preparation process of the hydrogel were the same as those described in Example 1.

[0067] Comparative Example 5

[0068] In this comparative example, wild silk fibroin (including tussah silk, ricinus silk, Bombyx mori silk and camphor silk, mixed in a mass ratio of 1:1:1:1) is used as raw material to prepare injectable hydrogel. The other components and preparation process of the hydrogel are the same as those described in Example 1.

[0069] Comparative Example 6

[0070] In this comparative example, aminated wild silk fibroin is used as raw material (tussah silk fibroin is preferred in this comparative example) to prepare injectable hydrogel. The other components and preparation process of the hydrogel are the same as those described in Example 1.

[0071] The preparation method of aminated wild silk fibroin is as follows: 1g of regenerated wild silk fibroin is configured into a solution with a concentration of 0.1-20% (preferably 2% in this embodiment), 0.01-1g of a cross-linking agent DMTMM (4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride) (Aladdin) or EDC / NHS (Aladdin) (DMTMM is preferred as a cross-linking agent in this comparative example because it is not affected by pH changes, and its dosage is 0.2g), and 0.01-1g of a small molecule that activates carboxyl and diamino groups (any one or more of adipic acid dihydrazide, spermidine, spermine, ethylenediamine, butanediamine, and hexamethylenediamine), preferably 0.2g of spermidine (Anhui Zesheng) in this embodiment, react for 1-48h (preferably 24h in this embodiment), and convert the carboxyl group of the wild silk fibroin into an amino group to thereby modify it by amination;

[0072] Example 3

[0073] This example compares the properties of the hydrogels prepared by the methods described in Example 1 and Comparative Examples 1 to 5, respectively. The steps for determining the properties of the hydrogels are the same as those described in Example 2. The specific results are shown in Table 1.

[0074] Table 1 Comparison of properties of hydrogels prepared from different silk fibroins

[0075]

[0076]

[0077] As can be seen from Table 1, the order of performance of hydrogels prepared from different silks is as follows: tussah silk (Example 1) > Bombyx mori fibroin (Comparative Example 3) > Cinnamomum camphora fibroin (Comparative Example 4) = Ricinus communis silk (Comparative Example 2) > Mulberry silk (Comparative Example 1), that is, no matter whether the wild silk fibroin in the hydrogel is of a single type or multiple types, its performance (modulus, adhesion, temperature sensitivity and gelation rate) is obviously better than that made from mulberry silk, mainly because its β-folding is composed of unstable polyalanine, which allows it to be assembled by temperature-driven assembly and then increase the modulus and adhesion properties of the material itself.

[0078] Furthermore, the wild silk fibroin is subjected to amination treatment (Comparative Example 6), that is, a higher concentration of amino groups reacts with the active ester or aldehyde group of the modified polysaccharide, which can greatly accelerate the gelation speed of the biomimetic glue, shortening it from 3min to 10s, but the mechanical properties after assembly will not be significantly improved, because the amination modification only increases the cross-linking sites of the hydrogel network, and the mechanics of the assembly is only related to the β-folding sequence of the wild silk fibroin. In short, the four wild silk fibroin proteins (tussah silk fibroin, ricin silk fibroin, cecropia silk fibroin and camphor silk fibroin) can all be used to prepare high modulus injectable hydrogels, and good results can be achieved without chemical modification of wild silk. Among them, tussah silk fibroin is preferred because of its wide source, low price and lighter color; if rapid in situ gelation is required, spermidine is preferably used for amination because it has good biological functions and biocompatibility, but it should be noted that amination modification does not increase the modulus of the hydrogel.

[0079] Example 4

[0080] This example explores the effects of polysaccharide types and their modification methods on hydrogel properties. The polysaccharides used are chondroitin sulfate, hyaluronic acid, and dextran; the modification methods are active esterification and oxidation; different polysaccharide modification methods are as follows:

[0081] (1) Active esterification modification: same as described in Example 1;

[0082] (2) Oxidative modification: prepare a 1-5% polysaccharide solution (preferably 5% in this embodiment), mix with 1-10g sodium periodate (preferably 10g in this embodiment), and react in the dark for 4-24h (preferably 24h in this embodiment); add 5-10mL polyethylene glycol to neutralize the excess sodium periodate (preferably 5mL in this embodiment), dialyze against 50% alcohol in the dark for 5 days to avoid excessive swelling, and then freeze-dry into powder for later use;

[0083] The other components and preparation method of the hydrogel are the same as those described in Example 1. The steps for determining the properties of the hydrogel are the same as those described in Example 2. The specific results are shown in Table 2.

[0084] Table 2 Comparison of hydrogel properties prepared by different modified polysaccharides

[0085]

[0086]

[0087] As shown in Table 2, the hydrogel properties (modulus, adhesion and compressive strength) prepared by wild silk with active esterified chondroitin sulfate are better than those prepared with other modified polysaccharides. This may be because chondroitin sulfate is rich in anions such as carboxyl and sulfonic acid groups, which can form salt bridge hydrogen bonds with the guanidine groups in wild silk; however, hyaluronic acid only has carboxyl groups, and dextran molecules have no anions, which makes it lack more intermolecular interactions relative to chondroitin sulfate; in addition, active esters react with amino groups of proteins to form stable amide bonds, while oxidized polysaccharides only form Schiff bonds with amino groups in tissues, which are unstable dynamic chemical bonds. In summary, from the perspective of polysaccharides, chondroitin sulfate>hyaluronic acid>dextran; from the perspective of modification, active esterification>oxidation.

[0088] Example 5

[0089] This example provides the use of the hydrogel prepared in Example 1 in treating cartilage defects.

[0090] A full-thickness cartilage defect of 10 mm*5 mm in area was constructed with a modeling device for the pig femoral cartilage. The hydrogel prepared in Example 1 was injected into the cartilage defect. When injected, the hydrogel was a viscous yellow transparent liquid. It was quickly assembled at room temperature and turned into a milky white opaque strong and tough hydrogel. It was pressed with a medicine spoon to ensure that it was fully assembled and tough. The solidification process lasted for about 3 minutes ( Figure 4 ); The hydrogel did not fall off when rubbed vigorously by hand, indicating that it has strong adhesion ( Figure 5 AB); using electron microscopy to observe the cartilage tissue repaired with the hydrogel for 5 minutes, it was found that the hydrogel and the cartilage tissue were still tightly attached to each other under microscopic conditions ( Figure 5 C), indicating that the hydrogel at this time plays a role in repairing and protecting cartilage tissue; at the same time, the compression performance of the instant gel was measured, and it could withstand a pressure of more than 100N ( Figure 6 ).

[0091] At the same time, a cartilage defect with a diameter of 4 mm and a height of 0.5 mm was constructed on the surface of the rabbit femur using a self-developed modeling device, and a hole with a diameter of 0.5 mm was drilled in the center of the cartilage defect to simulate clinical microfracture surgery; the hydrogel prepared in Example 1 was mixed with blood in the bone marrow cavity and injected into the cartilage defect. Figure 7 As shown, 12 weeks after the bionic glue was implanted, there was obvious cartilage-like tissue growing into the defect; histological images showed that the bionic glue can promote the repair of cartilage tissue very well, and the new tissue has a similar microstructure to the cartilage tissue, while the tissue regenerated by microfracture surgery is fibrous tissue without a directional structure.

[0092] Example 6

[0093] This example provides application of the hydrogel prepared in Example 1 in treating skin damage.

[0094] A 2.5 cm long full-thickness skin defect was cut on the back of the mouse using a scalpel, and the hydrogel prepared in Example 1 was injected into the skin injury (bionic glue group). The specific results are shown in Figure 8 . Compared with traditional sutures to repair skin injuries, bionic glue is gentler and does not require making sutures on the skin. After the wound heals, the sutures need to be removed. In clinical applications, it can not only simplify the treatment steps, but more importantly, it can relieve the patient's pain. In addition, bionic glue is more effective, that is, the wound heals after 7 days of treatment with bionic glue, and the color of the healed area is not much different from that of the surrounding skin. Therefore, it can be applied to skin injuries all over the body, especially delicate parts such as the face and hands. After 14 days, the wound treated with bionic glue turned into a shallow new skin, while the blank group was left with a deep scar. Although the suture group can also repair the damaged skin well, there are new wounds and scars at the sutures. In addition, compared with the repair effects of the blank group and the suture group, the repaired skin of the bionic glue group is smoother and the scars are smaller ( Fig. 9 ). Traditional adhesive hydrogels need to apply glue to the defect wound, but the high modulus strong adhesive hydrogel prepared in Example 1 can be applied to the skin surface and directly connect the skin to the skin by virtue of the high modulus colloidal properties to complete non-implantation repair. In summary, the high modulus strong adhesive hydrogel prepared in Example 1 shows excellent performance in practical applications, such as injectable, temperature-sensitive enhancement, high modulus, strong adhesion, lubrication, etc., and can be used to treat cartilage defects and skin injuries.

[0095] It can be understood that since the performance of the hydrogel prepared by using the other three wild silk fibroin proteins (castor silk, Bombyx mori silk and Cinnamomum camphora silk) or a mixture of the four wild silk fibroin proteins is equivalent to that of the hydrogel prepared from tussah silk (Example 3), its therapeutic effect is also consistent with that of the hydrogel prepared from tussah silk.

[0096] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high modulus, strong adhesion, injectable hydrogel, characterized in that: It is prepared by cross-linking wild silk and modified polysaccharides.

2. The hydrogel according to claim 1, characterized in that The wild silk includes any one or more of tussah silk, castor silk, ceramsite silk and camphor silk.

3. The hydrogel according to claim 2, characterized in that The modified polysaccharide comprises any one or more of active esterified chondroitin sulfate, active esterified hyaluronic acid, oxidized chondroitin sulfate, oxidized hyaluronic acid, oxidized dextran, oxidized cellulose and oxidized sodium alginate.

4. A method for preparing a high modulus, strong adhesion, injectable hydrogel, characterized in that: The preparation method is used to prepare the hydrogel according to any one of claims 1 to 3.

5. The preparation method according to claim 4, characterized in that: The fibroin solution of wild silk and the modified polysaccharide are mixed in proportion.

6. The preparation method according to claim 5, characterized in that: The concentration of the silk fibroin solution is 1-50% (w / w).

7. The preparation method according to claim 6, characterized in that: The mixing ratio of the silk fibroin solution to the modified polysaccharide is 1:1-1:

100.

8. A high modulus and strong adhesion biomimetic tissue glue, characterized in that: The bionic tissue glue comprises the hydrogel according to any one of claims 1 to 3, and the hydrogel is injectable and temperature-sensitive.

9. Use of a hydrogel for preparing a reagent for a cell mixture, characterized in that: The hydrogel is as described in any one of claims 1 to 3, the cells include any one or more of bone marrow mesenchymal stem cells, adipose mesenchymal stem cells, chondrocytes, synovial mesenchymal stem cells, fibroblasts, endothelial cells, epithelial cells, etc., and the cell mixture can be used to treat cartilage defects and skin injuries.

10. A use of wild silk for preparing an agent for improving the modulus of injectable hydrogels, characterized in that: The hydrogel modulus is 10 kPa-10 MPa.

Citation Information

Patent Citations

  • Injectable natural silk nanofiber composite hydrogel and preparation method thereof

    CN117586533A

Cited By

  • Silk fibroin composite gel and preparation method thereof

    CN120501932A

  • Silk fibroin composite gel and preparation method thereof

    CN120501932B